Direction of Associations between Added Sugar Intake in Early Childhood and Body Mass Index at Age 7 Years May Depend on Intake Levels - Herbst, Antje; Diethelm, Katharina; Cheng, Guo; Alexy, Ute; Icks, Andrea; Buyken, Anette (The Journal of Nutrition)

Validation of protein and potassium intakes assessed from 24 h recalls against levels estimated from 24 h urine samples in children and adolescents of Turkish descent living in Germany: results from the EVET! Study - Bokhof, Beate; Buyken, Anette; Doğan, Canan; Karaboğa, Arzu; Kaiser, Josa; Sonntag, Antje; Kroke, Anja (Public Health Nutrition)
Abstract Objective Nutrition-related health problems such as obesity are frequent among children and adolescents of Turkish descent living in Germany, yet data on their dietary habits are scarce. One reason might be the lack of validated assessment tools for this target group. We therefore aimed to validate protein and K intakes from one 24 h recall against levels estimated from one 24 h urine sample in children and adolescents of Turkish descent living in Germany. Design Cross-sectional analyses comprised estimation of mean differences, Pearson correlation coefficients, cross-classifications and Bland–Altman plots to assess the agreement between the nutritional intake estimated from a single 24 h recall and a single 24 h urine sample collected on the previous day. Setting Dortmund, Germany. Subjects Data from forty-three study participants (aged 5–18 years; 26 % overweight) with a traditional Turkish background were included. Results The 24 h recall significantly overestimated mean protein and K intake by 10·7 g/d (95 % CI of mean difference: 0·6, 20·7 g/d) and 344 mg/d (95 % CI 8, 680 mg/d), respectively. Correlations between intake estimates were r = 0·25 ( P = 0·1) and 0·31 ( P = 0·05). Both methods classified 70 % and 69 % of the participants into the same/adjacent quartile of protein and K intake and misclassified 7 % and 7 %, respectively, into the opposite quartile. Bland–Altman plots indicated a wide scattering of differences in both protein and K intake. Conclusions Among children and adolescents of traditional Turkish descent living in Germany, one 24 h recall may only be valid for categorizing subjects into high, medium or low consumers.

Associations between the macronutrient composition of the evening meal and average daily sleep duration in early childhood - Diethelm, Katharina; Remer, Thomas; Jilani, Hannah; Kunz, Clemens; Buyken, Anette (Clinical Nutrition)

Dietary glycaemic index and glycaemic load among Australian children and adolescents - Chun Yu Louie, Jimmy; Buyken, Anette; Heyer, Kristina; Flood, Victoria M. (British Journal of Nutrition)
There are no published data regarding the overall dietary glycaemic index (GI) and glycaemic load (GL) of Australian children and adolescents. We therefore aim to describe the dietary GI and GL of participants of the 2007 Australian National Children's Nutrition and Physical Activity Survey (2007ANCNPAS), and to identify the main foods contributing to their GL. Children, aged 2–16 years, who provided two 24 h recalls in the 2007ANCNPAS were included. A final dataset of 4184 participants was analysed. GI of each food item was assigned using a previously published method. GL was calculated, and food groups contributing to the GL were described by age group and sex. The weighted mean dietary GI and GL of the participants were 54 ( sd 5) and 136 ( sd 44), respectively. Among the nutrients examined, Ca had the highest inverse relationship with GI ( P < 0·001), while percentage energy from starch was most positively associated with GI. The association between fibre density and GI was modest, and percentage energy from sugar had an inverse relationship with GI. Daily dietary GL contributed by energy-dense and/or nutrient-poor (EDNP) items in subjects aged 14–16 years was more than doubled that of subjects aged 2–3 years. To conclude, Australian children and adolescents were having a high-GI dietary pattern characterised by high-starchy food intake and low Ca intake. A significant proportion of their dietary GL was from EDNP foods. Efforts to reduce dietary GI and GL in children and adolescents should focus on energy-dense starchy foods.

Consumption of dietary salt measured by urinary sodium excretion and its association with body weight status in healthy children and adolescents - Libuda, Lars; Kersting, Mathilde; Alexy, Ute (Public Health Nutrition)
Abstract Objective Highly processed foods such as convenience foods usually have a high salt content and therefore might indirectly act as adipogenic due to an increasing consumption of sugar-containing beverages (SCB). We examined the association between dietary salt and body weight status. Design We used data on urinary Na excretion as an indicator of dietary salt and BMI standard deviation score (BMI-SDS) and percentage body fat (%BF) of children and adolescents participating in the DONALD (Dortmund Nutritional and Anthropometric Longitudinally Designed) Study. Setting Dortmund, Germany. Subjects Children and adolescents ( n 364) who had at least two 24 h urine samples and two dietary records in the observational period between 2003 and 2009 were considered in our data analysis. Results Repeated-measures regression models revealed that urinary Na was positively associated with BMI-SDS (+0·202 SDS/g Na excretion at baseline; P < 0·001) and %BF (+1·303 %BF/g Na excretion at baseline; P < 0·01) at baseline in boys and girls. These associations remained significant after adjustment for SCB consumption and total energy intake. Furthermore, there was a positive trend between baseline Na excretion and the individual change in %BF in the study period (+0·364 increase in %BF/g Na excretion at baseline), which was confirmed after inclusion of SCB consumption or total energy intake. There was no significant association between the change in Na excretion and the concurrent change of either BMI-SDS or %BF in any model. Conclusions Our results suggest that a high intake of processed salty foods could have a negative impact on body weight status in children and adolescents independently from their consumption of SCB.

24h-Sodium excretion and hydration status in children and adolescents - Results of the DONALD Study - Alexy, Ute; Cheng, Guo; Libuda, Lars; Hilbig, Annett; Kersting, Mathilde (Clinical Nutrition)

Ansätze der Übergewichtsprävention durch verbessertes Trinkverhalten im Setting Grundschule - Muckelbauer, R.; Libuda, Lars; Clausen, K.; Kersting, M. (Bundesgesundheitsblatt - Gesundheitsforschung - Gesundheitsschutz)

Fluids and children’s health. - Muckelbauer, R.; Libuda, Lars; Kersting, M. (Developing Children´s Food Products.)

Prepubertal Glucocorticoid Status and Pubertal Timing - Shi, Lijie; Wudy, Stefan A.; Buyken, Anette; Maser-Gluth, Christiane; Hartmann, Michaela F.; Remer, Thomas (The Journal of Clinical Endocrinology & Metabolism)
Context: Whether prepubertal glucocorticoid status impacts on the timing of puberty is not clear. Objective: The objective of the study was to examine the relationship between prepubertal glucocorticoid status and early or late pubertal markers, independent of adrenarchal and nutritional status. Design and Participants: Prospective cohort study of healthy Caucasian children (n = 111, 56 boys) who provided both 24-h urine samples and weighed dietary records 1 and 2 yr before the start of pubertal growth spurt [age at take-off (ATO)]. Measurements: Major urinary glucocorticoid and androgen metabolites determined by gas chromatography-mass spectrometry analysis were summed to assess daily overall cortisol (ΣC21) and adrenal androgen secretion; urinary free cortisol and cortisone measured by RIA were summed (UFF+UFE) as an indicator of potentially bioactive free glucocorticoids. Main Outcomes: The main outcomes included ATO, age at peak height velocity, age at menarche/voice break, ages at Tanner stage 2 for breast (girls) and genital (boys) development, and pubic hair. Results: In girls ΣC21, but not UFF+UFE, was associated with pubertal markers after adjusting for overall adrenal androgen, urinary nitrogen, and body fat. Girls with higher ΣC21 (fourth quartile) reached ATO 0.7 yr (P = 0.01) and menarche 0.9 yr later (P = 0.006) than girls with lower ΣC21 (first quartile). The ΣC21 tended to be also positively associated with age at Tanner stage 2 for breast (P = 0.1), Tanner stage 2 for pubic hair (P = 0.1), and age at peak height velocity (P = 0.06). In boys, neither the ΣC21 nor UFF+UFE was related to pubertal timing. Conclusion: An individually higher prepubertal glucocorticoid secretion level, even in physiological range, appears to delay early and late pubertal timing of healthy girls, particularly their onset of pubertal growth spurt and menarche.

Longitudinal associations between reported sleep duration in early childhood and the development of body mass index, fat mass index and fat free mass index until age 7 - Diethelm, Katharina; Bolzenius, Katja; Cheng, Guo; Remer, Thomas; Buyken, Anette (International Journal of Pediatric Obesity)

Consumption of polyunsaturated fatty acids, fish, and nuts and risk of inflammatory disease mortality - Gopinath, Bamini; Buyken, Anette; Flood, Victoria M; Empson, Marianne; Rochtchina, Elena; Mitchell, Paul (The American Journal of Clinical Nutrition)

Association of dietary energy density in childhood with age and body fatness at the onset of the pubertal growth spurt - Günther, Anke L. B.; Stahl, Lisa J.; Buyken, Anette; Kroke, Anja (British Journal of Nutrition)
The aim of the present study was to examine the association of pre-pubertal dietary energy density (ED) with both age and body fatness at the start of the pubertal growth spurt (age at take-off, ATO). Analyses included 219 DOrtmund Nutritional and Anthropometric Longitudinally Designed Study participants with sufficient height measurements to estimate ATO who provided 3 d weighed dietary records at baseline, i.e. 2 and 3 years before ATO (mean age 6·9 ( sd 1·2) years). Mean energy intakes and amounts of foods/drinks consumed at baseline were derived from the records. ED (kJ/g) was calculated based on (1) all foods and drinks (ED_all), (2) foods and energy-containing drinks (ED_energy), (3) foods and milk as a drink, but no other beverages (ED_milk) and (4) foods only, solid or liquid (ED_food). Using multiple regression analyses, the association between the ED variables and ATO was investigated. Furthermore, Z -scores of BMI and fat mass index (FMI) at ATO were considered as outcomes to reflect body fatness at puberty onset. The results showed that ED at baseline was not associated with ATO, regardless of the ED method used. For example, mean ATO in the lowest v. highest tertile of ED_food was 9·3 (95 % CI 9·0, 9·5) v. 9·4 (95 % CI 9·1, 9·7) years, P trend = 0·8 (adjusted for sex, maternal age, birth weight, dietary protein, dietary fibre, baseline BMI Z -score). Similarly, ED was not independently associated with BMI or FMI Z -score at ATO ( P trend = 0·3–0·9). In conclusion, dietary ED in childhood did not influence timing or body fatness at ATO in this cohort of healthy, free-living children.

Regional and socio-economic differences in food, nutrient and supplement intake in school-age children in Germany: results from the GINIplus and the LISAplus studies - Sausenthaler, Stefanie; Standl, Marie; Buyken, Anette; Rzehak, Peter; Koletzko, Sibylle; Bauer, Carl Peter; Schaaf, Beate; von Berg, Andrea; Berdel, Dietrich; Borte, Michael; Herbarth, Olf; Lehmann, Irina; et al. (Public Health Nutrition)
Abstract Objective To describe regional differences between eastern and western Germany with regard to food, nutrient and supplement intake in 9–12-year-old children, and analyse its association with parental education and equivalent income. Design Data were obtained from the 10-year follow-up of the two prospective birth cohort studies – GINIplus and LISAplus. Data on food consumption and supplement intake were collected using an FFQ, which had been designed for the specific study population. Information on parental educational level and equivalent income was derived from questionnaires. Logistic regression modelling was used to analyse the effect of parental education, equivalent income and region on food intake, after adjusting for potential confounders. Setting Germany. Subjects A total of 3435 children aged 9–12 years. Results Substantial regional differences in food intake were observed between eastern and western Germany. Intakes of bread, butter, eggs, pasta, vegetables/salad and fruit showed a significant direct relationship with the level of parental education after adjusting for potential confounders, whereas intakes of margarine, meat products, pizza, desserts and soft drinks were inversely associated with parental education. Equivalent income had a weaker influence on the child's food intake. Conclusions Nutritional education programmes for school-age children should therefore account for regional differences and parental education.

Prevention strategies for type 2 diabetes should be based on evidence-based medical nutrition data. Reply to Uusitupa M, Lindström J, Tuomilehto J [letter] - Buyken, Anette; Mitchell, P.; Ceriello, A.; Brand-Miller, J. (Diabetologia)

The glycemic index issue - Brand-Miller, Jennie; Buyken, Anette (Current Opinion in Lipidology)

Den Umgang mit Geld und Konsum lernen – Verbraucherbildung in der Schule - Schlegel-Matthies, Kirsten (Stimme der Familie)

Was ist Verbraucherbildung? – Was kann sie leisten? - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Ernährungssozialisation und -bildung und die Entstehung einer "kulinarischen Vernunft" - Schlegel-Matthies, Kirsten; Methfessel, Barbara; Heindl, Ines (Die Zukunft auf dem Tisch. Analysen, Trends und Perspektiven der Ernährung von morgen)

Ernährung und Diätetik - Schlegel-Matthies, Kirsten; Methfessel, Barbara ("Gesunde Lebensführung" - kritische Analyse eines populären Konzepts)

Mahlzeit im Wandel - die Entideologisierung einer Institution - Schlegel-Matthies, Kirsten (Mahlzeiten. Alte Last oder neue Lust?)